(untitled) (Homoeopathy for All, 2026)
Homeopathy emphasizes individu alization through constitutional pre scribing, where treatment is guided by the totality of physical, mental, and emotional symptoms. The repertory serves as a systematic bridge between case taking and Materia Medica, en abling logical remedy selection. This article explores the philosophical and clinical role of the repertory in consti tutional prescribing, its evolution, ap plications in chronic cases, and limita tions in modern practice.